THE INFLUENCE OF AUDIO VISUAL MEDIA ON STUDENTS’ LEARNING INTEREST TO IMPROVE THEIR LEARNING OUTCOMES - Dwi Agustin; Marleni; Henni Riyanti (Universitas PGRI Palembang, 2024)
This research is motivated by students' low interest in learning because in the teaching and learning process teachers tend to use tools in the form of simple media, making it less interesting for students to pay attention to. This research aims to determine the effect of audio-visual media on class IV students' interest in learning in SBdP subjects. This research was carried out at SD Negeri 166 Palembang which is located on Jl. Rimba Kemuning Lr. Buyut, Kemuning District, Palembang City, South Sumatra. This research is a type of experimental research, namely the Quasi Experimental Design type. The population and sample in this study were fourth grade students at SD Negeri 166 Palembang, totaling 29 students in the control class and 26 students in the experimental class. Data collection techniques in this research are observation, questionnaires and documentation. Data analysis techniques in this research include Normality Test, Homogeneity Test, Hypothesis Test. The results of this research are hypothesis testing showing that t count ≥ t table or 4.706 ≥ 1.674 so it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of audio visual media on class IV students' interest in learning in SBdP subjects.